2003
DOI: 10.1007/s00330-002-1564-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metallic dental implants on CT-based attenuation correction in a combined PET/CT scanner

Abstract: Our objective was to study the effect of metal-induced artifacts on the accuracy of the CT-based anatomic map as a prerequisite for attenuation correction of the positron emission tomography (PET) emission data. Twenty-seven oncology patients with dental metalwork were enrolled in the present study. Data acquisition was performed on a PET/CT in-line system (Discovery LS, GE Medical Systems, Milwaukee, Wis.). Attenuation correction of emission data was done twice, using an 80-mA CT scan (PET(CT80)) and a (68)Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 13 publications
(10 reference statements)
5
84
1
5
Order By: Relevance
“…This effect was greater in the lateroinferior, inferolateral and inferoseptal regions. This is in agreement with the observations of Goerres et al [8,24] and Kamel et al [9] who found that PET artefacts arising from metallic materials in PET/CT oncological imaging were more pronounced near the metallic components. It would be expected that the magnitude and extension of metallic artefacts particularly in patients with ICD leads are correlated with the closeness of the ICD to the left ventricle [5], the number of leads used in the patients and the metal used for metallic components.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This effect was greater in the lateroinferior, inferolateral and inferoseptal regions. This is in agreement with the observations of Goerres et al [8,24] and Kamel et al [9] who found that PET artefacts arising from metallic materials in PET/CT oncological imaging were more pronounced near the metallic components. It would be expected that the magnitude and extension of metallic artefacts particularly in patients with ICD leads are correlated with the closeness of the ICD to the left ventricle [5], the number of leads used in the patients and the metal used for metallic components.…”
Section: Discussionsupporting
confidence: 93%
“…Metallic implants produce streak artefacts on CT images and therefore affect the generated μ-maps and attenuationcorrected PET images in PET/CT imaging [9,24]. Since the CT images are used for attenuation correction of the PET images in CTAC, the propagation of these artefacts to the PET images is the main concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implanted materials, e.g. dental or orthopaedic implants, are often present in patients and lead to artificial AC, resulting in overestimation or underestimation of tracer uptake in PET/CT studies [2][3][4]. The integration of PET and MRI into one imaging modality (PET/MRI) necessitated MRI-based attenuation correction (MRAC).…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Metallic objects, such as prostheses [53] and dental implants [54], also complicate the use of CTbased attenuation correction. CT transmission scans are more prone to produce strong artifacts around metallic objects than the common PET transmission scans.…”
Section: Additional Challenges For Ct-based Attenuation Correctionmentioning
confidence: 99%